Reducing power sector emissions under the 1990 Clean Air Act Amendments: A retrospective on 30 years of program development and implementation - LaCount, Melanie D.; Haeuber, Richard A.; Macy, Taylor R.; Murray, Beth A. (Atmospheric environment (1994), 2021)
The 1990 Clean Air Act Amendments (CAAA) launched a new era in environmental protection. New provisions created the innovative Acid Rain Program to curtail acid-rain-causing emissions from the electric power sector through an allowance trading program. Success implementing this new type of program led to its expanded use to achieve additional power plant emission reductions in support of the CAAA "Good Neighbor" requirements. As a result, air pollution and its environmental effects have decreased dramatically in the last 30 years. Implementation of power plant regulations under the acid rain and Good Neighbor provisions of the CAAA provides insights into the efficacy of legislative versus regulatory policy and holds valuable lessons for future environmental policy. •The 1990 Clean Air Act Amendments launched a new era in environmental protection.•The Acid Rain Program's allowance trading program revolutionized air quality policy.•This success spurred additional programs to address interstate transport of power plant emissions.•Air pollution and environmental effects have decreased dramatically since 1990.•Thirty years of implementation experience offers key environmental policy insights.